Role Of Prosecutor General Prosecution Of Actors In The Implementation Of Abuse Of Narcotics Crime (Case Study in Magelang District Attorney) - Arif Hidayat; Sri Endah Wahyuningsih (Jurnal Daulat Hukum, 2018)
Prosecutor as one of the law enforcement agencies in Indonesia have a role in the prosecution, it is stipulated in Article 2 (1) of the Constitution of the Republic of Indonesia Number 16 of 2004 on the Prosecutor of the Republic of Indonesia. Prosecution is the act of the General Prosecutor for criminal matters delegated authority to the District Court in the case and in the manner set forth in the criminal procedure law to demand that tried and sentenced by the judge at the hearing. Drug abusers are people who use narcotics without authority or unlawfully. This study uses empirical juridical approach with descriptive analytical research specifications, types and sources of data are the primary data by conducting interviews and secondary data by performing a literature study, data analysis method logically and systematically. The results showed that the procedure includes the step prapenuntutan prosecution, prosecution and execution. The role of the public prosecutor in the criminal case handling drug abuse is a public prosecutor. Factors inhibiting the role of the public prosecutor in the prosecution that the case file is not yet complete, the type of drug is not on the list of narcotics, modus operandi vary and calling witnesses when the examination before the court, while the effort to overcome that by making the sharing of information between law enforcement, conduct legal counseling, attended a special training program narcotic crime and Attorney for School.Keywords: Role; Prosecution; Narcotics Abusers.